The importance of reading in the classroom (Research, Society and Development, 2021)
The principle of reading is to stimulate students' imagination, thus being able to set goals in order to achieve other objectives, such as educating, instructing and developing intelligence. Use as a starting point to teach some content, as they incorporate characters. This facilitates learning. Caring for the initial training of readers is essential when curating works, as children must have access to appropriate books that talk to their age group and can also take the opportunity to take the content into the student's daily life, problem situations, promoting culture and educational information by encouraging reading, aiming to transform the task of teaching into art. And throughout its development, the child goes through a series of discoveries. Among the various materials that serve to support the process of child development, we have books, doors to the imaginary world and make-believe, which makes the child dive into an adventure of knowledge, knowledge, discoveries that reading can offer in addition to transmitting new values and knowledge to them, contributing positively to their growth and well-being.